HINDU-BUDHA-ISLAM CULTURAL ACCULTURATION IN INDONESIAN NATIONAL HISTORY TEXTBOOKS - Suryana, Yanyan (Universitas Pendidikan Indonesia, 2017)
The development of acculturation of Hindu, Buddhist and Islamic cultures in Indonesia is studied as a part of Indonesian national historical textbooks. In order to understand and discover the elements of acculturation in historical events, this study is conducted based on the historical textbook theory and cultural acculturation theory. This study is aimed at finding the relationship and values in historical education. Critical discourse analysis is used as a method of analysis to unveil the acculturation values contained on history textbooks in schools. Hence, the study results showed that there is a relation between textual study of history textbooks and the acculturation of Hindu, Buddha and Islam culture.